THE FASCINATING MATHEMATICAL BEAUTY OF THE SUM OF SQUARES - Mulatu, Lemma; Lord, Keith (IJRDO -JOURNAL OF MATHEMATICS, 2018)
We will investigate which integers can be written as the sum of squares. Different examples are given to supplement each given theorems.